Adherence in the reinforced concrete with bamboo - Vargas Vásquez, Wilder Roger (2020)
The world, research on the use of bamboo as a concrete reinforcement has achieved an improvement in reducing water absorption. However, no better adherence has been achieved between these elements. Therefore, the objective of this research was to propose other alternative treatments to the bamboo surface to improve adhesion efforts with concrete. Initially, physical and mechanical tests were carried out to determine the characteristics of the bamboo used. Subsequently, adherence tests were continued, for which specimens were made (4 “x8” concrete specimens embedded in their interior and at different depths bamboo slats waterproofed with RC-250 liquid asphalt). The slats were smooth and ribbed with a medium sand attachment. Then the bond strength values were determined. Finally, bamboo-reinforced beams were made which were subjected to bending tests. The results showed a better performance of the ribbed and waterproofed slats with asphalt and medium sand additive. A bond strength of 6,7 kg / cm2 was achieved on the bamboo reinforced beams. This presents an increase of the order of 2,5 times the tensile strength compared to a beam without reinforcement.